Can an Enactivist Approach Entail the Extended Conscious Mind? - Qiantong Wu (Rosenberg & Sellier, 2018)
This paper discusses the enactivist attempt to entail the hypothesis of extended conscious mind (ECM). The enactists suggest that conscious experience is a relational interaction between the subject and the external environment; this personal-level description of conscious experience naturally entails an extended sub-personal characterization of the material basis of conscious experience (i.e. the ECM). However, in this paper, I am going to argue that the enactivist description at the personal level is still open to an internalist challenge at the sub-personal level. In response to this challenge, I suggest combining enactivism with the concept of predictive processing, delineating a sub-personal characterization of conscious experience that corresponds to the enactivist interpretation at the personal level.